Primary Genital Herpes Simplex Virus Type I in Preterm Prelabour Rupture of Membranes at 30 Weeks' Gestation - Anna Dalton; Rosalie Grivell (Hindawi Limited, 2015)
Background. Disseminated herpes simplex virus (HSV) in the neonate is associated with significant morbidity and mortality. Current guidelines recommend caesarean in third-trimester maternal primary genital HSV outbreaks to prevent transmission from mother to fetus. In the premature fetus, however, expectant management is often necessary to reduce morbidity of prematurity. The benefit of performing caesarean after 6 hrs of rupture of membranes (ROM) to reduce maternal-fetal transmission is unclear. Case. A female patient with primary genital HSV type 1 outbreak coinciding with preterm, prelabour rupture of membranes (PPROM) at 30 + 3 weeks' gestation. An immediate caesarean section was not performed after multidisciplinary team discussion due to the benefits of glucocorticoids on immune complications of prematurity. The patient had expectant management for 5 days with intravenous (IV) aciclovir and then delivered an infant vaginally with disseminated neonatal HSV. Conclusion. We address the rare presentation of primary HSV infection associated with PPROM and the dilemma of how to manage these patients given the limited literature. We discuss the role of intrauterine compartment monitoring with amniocentesis, the mode of delivery when ROM has occurred for 120 hours, expectant management to reduce prematurity, and the effectiveness of aciclovir to reduce viral shedding in the prevention of neonatal HSV.